Method availability and the prevention of suicide: a re-analysis of secular trends in Britain, 1950-1975 - Gunnell, David J.; Middleton, Nicos; Frankel, Stephen J. (My University, 2000)
Background: In England and Wales in the 1960s there were marked declines in suicide rates. These reductions were partly attributable to the detoxification of the domestic gas supplies; however, their extent varied by age and gender, with the most striking effects seen in older men. The objective of this study was to investigate method-specific trends in suicide between 1950 and 1975 to elucidate possible explanations for the patterns seen in different demographic groups. Methods: An analysis of age-standardised method-specific suicide rates for England and Wales between 1950 and 1975 was carried out using routinely available mortality and population statistics. Results: As has previously been shown, there were marked reductions in suicides by gassing in men and women of all ages between 1960 and 1975. In women and younger men, the effects of these reductions on overall suicide rates were partially offset by rises in drug overdose deaths (method substitution), but there were no immediate increases in the use of other suicide methods. In contrast, in older men, reductions in suicide by gassing were accompanied by only a slight increase in overdose suicides as well as reductions in rates of suicide using all other methods. The modest rise in overdose fatalities in older men occurred despite the fact that they were more often prescribed barbiturates and tricyclic antidepressants than younger men. Conclusions: Accessibility to and the lethality of particular methods of suicide may have profound effects on overall suicide rates. Such effects appear to depend upon the popularity of the method and the extent to which alternative methods that are acceptable to the individual are available. Social and psychological interpretations of fluctuations in suicide rates should only be made after assessing the possible contribution to these of changes in method availability and lethality.
Keywords: Suicide; Method availability; Lethality